ATTITUDES TOWARDS EUTHANASIA AND ASSISTED SUICIDE: A COMPARISON BETWEEN PSYCHIATRISTS AND OTHER PHYSICIANS. (12th April 2012) - LEVY, TAL BERGMAN; AZAR, SHLOMI; HUBERFELD, RONEN; SIEGEL, ANDREW M.; STROUS, RAEL D.
ABSTRACT: Euthanasia and physician assisted‐suicide are terms used to describe the process in which a doctor of a sick or disabled individual engages in an activity which directly or indirectly leads to their death. This behavior is engaged by the healthcare provider based on their humanistic desire to end suffering and pain. The psychiatrist's involvement may be requested in several distinct situations including evaluation of patient capacity when an appeal for euthanasia is requested on grounds of terminal somatic illness or when the patient is requesting euthanasia due to mental suffering. We compare attitudes of 49 psychiatrists towards euthanasia and assisted suicide with a group of 54 other physicians by means of a questionnaire describing different patients, who either requested physician‐assisted suicide or in whom euthanasia as a treatment option was considered, followed by a set of questions relating to euthanasia implementation. When controlled for religious practice, psychiatrists expressed more conservative views regarding euthanasia than did physicians from other medical specialties. Similarly female physicians and orthodox physicians indicated more conservative views. Differences may be due to factors inherent in subspecialty education. We suggest that in light of the unique complexity and context of patient euthanasia requests, based on their training and professional expertise psychiatrists are well suited to take a prominent role in evaluating such requests to die and making a decision as to the relative importance of competing variables.